PROGRAM “PERAHU”: MODEL EDUKASI PARTISIPATIF UNTUK PENINGKATAN KAPASITAS KADER PMR DALAM PENCEGAHAN HIV-AIDS - Yusuf Omar Setyoadji; Valensia Mutiara Anisa Putri; Muhammad Ilham Danny; Vanessa Christabel; Zahra Naura Herdita; Srestha Indra Cahya; Rivia Risdandini; Alidha Nur Rakhmani (Universitas Nusa Bangsa, 2025)
HIV-AIDS remains a major global public health challenge and a leading cause of mortality in developing countries, including Indonesia. At the local level, prevention and early detection services still show considerable gaps. As a vulnerable group, adolescents contribute a substantial portion of new cases, making school-based education an important prevention strategy. This community service initiative aims to evaluate the success of the PERAHU Program (Enhancing Reproductive Health and HIV/AIDS Education for Adolescents through Humanization and Cadre Development Efforts) as a multimodal educational model that combines interactive education, reflective simulation, and advocacy. The target participants were 42 Red Cross Youth (PMR) members at SMPN 2 Wagir, Wagir District, Malang Regency, using a pre-experimental one-group pretest-posttest design. All participants completed the program (100% attendance), with the average score increasing from 73.33 to 93.57 and the median score rising from 75 to 90. The PERAHU Program effectively enhanced peer educators’ knowledge and strengthened school support for the sustainability of HIV-AIDS education, indicating its potential as a participatory model to support HIV elimination goals in Indonesia.